Effectiveness of safety, health and environment practice in manufacturing industries: A case study of spray booth area at selected company in Kota Damansara, Selangor / Farah Amalina Ahmad Suhaimi - Farah Amalina , Ahmad Suhaimi (2018)
These days, accident and health diseases related to work become well known as a major concerned to the industries involved in Malaysia. This problem normally happened to manufacturing industry’s workers. The total number of organizations increased worldwide accommodate to this requirements of Occupational Health and Safety Management Systems (OHSMS). In Malaysia, the Occupational Safety and Health Act (OSHA, 1994) was made and the Occupational health and safety regulations enforce a punishment related to the unsafe working condition to the employer’s non-compliance with the standards. Painting industries, the effectiveness of Occupational Safety and Health practice in Malaysia is generally lacking and needs to be strengthen. One way to measure its effectiveness is by conducting audit checklist and questionnaire in the selected company referring to the OSHA 1994. Therefore, this research aim to observe the effectiveness of safety, health and environment practice by using a set of audit sheet, analyse the waste water and identify the awareness level of worker on through a set of questionnaires. Initially this organization measure effectiveness total of 71% complied with Occupational Safety and Health Act 1994. The waste water is fulfilled the minimum Environmental Requirement of Department of Environment (DOE), Malaysia with temperature (24.5 oC), pH (6.8), Biological Oxygen Demand (6.8mg/L), Chemical Oxygen Demand (8.9mg/L) and suspended Solids (ND < 1.0mg/L). Unfortunately, there is a room for improvement on the awareness aspect when a moderate correlation between the knowledge and attitudes (Correlation = 0.419, n=50, P= < 0.002)